2015
DOI: 10.1177/1932296815573864
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Model of the Transport of Fast-Acting Insulin From the Subcutaneous and Intradermal Spaces to Blood

Abstract: Pharmacokinetic (PK) models describing the transport of insulin from the injection site to blood assist clinical decision making and are part of in silico platforms for developing and testing of insulin delivery strategies for treatment of patients with diabetes. The ability of these models to accurately describe all facets of the in vivo insulin transport is therefore critical for their application. Here, we propose a new model of fast-acting insulin analogs transport from the subcutaneous and intradermal spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Intradermal Insulin. The model of intradermal insulin route is based on Lv et al 33 This model (equations A18, A19) has been identified on 10 healthy subjects, and assumes that insulin delivered at the intradermal site is then transported to the bloodstream via two independent routes, that is, a diffusion-like process and a combination of a diffusion-like processes followed by an additional compartment before entering the blood. Inhaled Insulin.…”
Section: Insulin Delivery Modelsmentioning
confidence: 99%
“…Intradermal Insulin. The model of intradermal insulin route is based on Lv et al 33 This model (equations A18, A19) has been identified on 10 healthy subjects, and assumes that insulin delivered at the intradermal site is then transported to the bloodstream via two independent routes, that is, a diffusion-like process and a combination of a diffusion-like processes followed by an additional compartment before entering the blood. Inhaled Insulin.…”
Section: Insulin Delivery Modelsmentioning
confidence: 99%
“…It is expected to improve the in silico development and testing of insulin treatment strategies, including AP systems. 25 Diabetes Management With BGM Systems. As it is important to ensure reliability of glucose measurements, there are a number of models that investigate the accuracy of BGM systems and relations to diabetic management.…”
Section: Metabolic and Measurement Modelsmentioning
confidence: 99%
“…It is expected to improve the in silico development and testing of insulin treatment strategies, including AP systems. 25…”
Section: Current Statusmentioning
confidence: 99%
“…Additionally, multicompartment input models have been shown to have better fit to actual clinical PK data, implying parallel uptake pathways. 38,39 This implies that insulin absorption via the lymph may be an underappreciated aspect of insulin uptake. In addition, vascular and lymphatic capillary densities within the tissue, molecular diffusion rates through the extracellular matrix, dissociation rates of various insulins and their specific formulation dependence, and local cellular utilization or degradation may also all contribute to the total uptake during SIA.…”
Section: Absorption Of Insulin Via the Lymphatic System And Effects Omentioning
confidence: 99%